America’s religious wars: the embattled heart of our public life - Sands, Kathleen M. (Yale University Press, 2019)
When Americans fight about "religion," we are also fighting about our conflicting identities, interests, and commitments. Religion-talk has been a ready vehicle for these conflicts because it is built on enduring contradictions within our core political values. The Constitution treats religion as something to be confined behind a wall, but in public communications, the Framers treated religion as the foundation of the American republic. Ever since, Americans have translated disagreements on many other issues into an endless debate about the role of religion in our public life. Built around a set of compelling narratives--George Washington's battle with Quaker pacifists; the fight of Mormons and Catholics for equality with Protestants; Teddy Roosevelt's concept of land versus the Lakota's concept; the creation-evolution controversy; and the struggle over sexuality--this book shows how religion, throughout American history, has symbolized, but never resolved, our deepest political questions